Identification, molecular docking, and kinetic studies of six novel angiotensin-I-converting enzyme (ACE) inhibitory peptides derived from Kenaf (Hibiscus cannabinus L.) seed - Zaharuddin, Nurul Dhania; Barkia, Ines; Wan Ibadullah, Wan Zunairah; Zarei, Mohammad; Saari, Nazamid (Elsevier, 2022)
Kenaf (Hibiscus cannabinus L.) seed is a valuable protein source that could be used to prepare protein hydrolysates with antihypertensive properties. However, the potential of using kenaf seeds for health food and pharmaceutical applications has not been fully exploited. Thus, the aim of this study was to identify and characterise the Angiotensin-I-Converting Enzyme (ACE) inhibitory peptides derived from the optimized hydrolysis conditions of kenaf seed protein hydrolysates (KSPH). The optimum hydrolysis conditions determined by response surface methodology (RSM) were as follows: temperature 65 °C, pH 6.5, hydrolysis time 2.25 h, and enzyme/substrate (E/S) ratio of 0.03 (w/w). Under these conditions, the degree of hydrolysis (DH) was 55.28 % and ACE inhibitory activity was 75.51 %. Also, the low molecular weight peptide fractions, <2 kilodalton (kDa) and 2–5 kDa showed the highest ACE-inhibitory activity (82.27 % and 83.69 %, respectively). The 2–5 kDa fraction by Quadrupole-Time-of-Flight Liquid Chromatography-Mass Spectrometry (QTOF LC − MS) revealed the abundance of six peptides, LYWSYLYN, ALFYWVS, LLLHAL, AKSCVVFP, INPPSTTN, and WTIPTPS. Kinetic studies showed that peptide LYWSYLYN possessed the highest Michaelis constant (Km), maximum velocity (Vmax) values and the lowest inhibitor constant (Ki) values, suggesting of its superior ACE inhibitory activity compared to other peptides.